Well-Being and Entrepreneurship Intention: An Empirical Study of New Perspectives - Contreras-Barraza, Nicolás; Acuña-Duran, Eduardo; Oyanedel, Juan Carlos; Salazar-Sepúlveda, Guido; Vega-Muñoz, Alejandro; Ariza-Montes, Antonio (Sustainability, 2022)
The research aims to examine the relationships between the constructs of entrepreneurial intention according to the theory of planned behavior (TPB) model and subjective well-being (SW). The model used considers the works proposed by Liñán and Chen and Oyanedel, Vargas, and Paez, and a questionnaire was applied to 1043 people in an urban population of the three main regions of Chile using multivariate statistical methods for its analysis (structural equation models). The proposed hypotheses are that subjective well-being towards entrepreneurship has a direct and positive effect on entrepreneurial intention (H1), personal attitude towards entrepreneurship has a direct and positive effect on entrepreneurial intention (H2), perceived behavioral control towards entrepreneurship has a direct and positive effect on entrepreneurial intention (H3), and subjective norm towards entrepreneurship has a direct and positive effect on entrepreneurial intention (H4). The results indicate that subjective well-being on entrepreneurial intention shows indirect effects mediated by subjective norm, contributing to the theoretical development concerning well-being incidence on entrepreneurial behavior, providing theoretical elements that can serve as a basis for further strengthening the understanding of the relationships between personal well-being, economic growth, and the harmonious relationship with the environment.